Quality variation of kilishi from different locations in Nigeria (2006)
Kilishi is an intermediate moisture meat that has a suitable concentration of dissolved solids that binds the moisture in it sufficiently to inhibit the growth of spoilage organisms. Samples of kilishi were collected from three different locations [Abuja (FCT), Kaduna (Kaduna state) and Ibadan (Oyo state)], a fourth sample was prepared in the laboratory to serve as control in a completely randomized design. Samples were packaged in three different media viz; aluminum foil (AF), transparent polyvinyl chloride bags (PVC) and transparent plastic containers with lids (PC). 100g of kilishi samples was packaged into each medium and left at ambient temperature (30-38°). The least moisture content of 6.98±0.65% was observed in the control, which differed significantly (P<0.05) from moisture contents of other samples. No difference (P>0.05) was observed for moisture between kilishi from Abuja and Kaduna. The mean crude protein content varied from 47.98±1.74 to 59.32±0.36%. All values reported differed significantly (P<0.05) from one another. For ether extract, the least value was I4.90±0.87%, while the highest was 15.75±0.36%. The PVC packaging contained the lowest microbial load of 3.18±0.01cfu/g for Kaduna kilishi at the onset of storage followed closely by the Ibadan kilishi. Three bacteria spp were isolated from the kilishi samples from the different locations. The isolates were identified as Bacillus subtilis, Bacillus pumilus, and Staphylococcus spp.